8-Oxoguanine DNA glycosylase-1-driven DNA base excision repair. Issue 1 (February 2015) - Ba, Xueqing; Aguilera-Aguirre, Leopoldo; Sur, Sanjiv; Boldogh, Istvan
<x xml:space="preserve">Abstract</x> Purpose of review To provide both an overview and evidence of the potential cause of oxidative DNA base damage and repair signaling in chronic inflammation and histological changes associated with asthma. Recent findings Asthma is initiated/maintained by immunological, genetic/epigenetic, and environmental factors. It is a world-wide health problem, as current therapies suppress symptoms rather than prevent/reverse the disease, largely due to gaps in understanding its molecular mechanisms. Inflammation, oxidative stress, and DNA damage are inseparable phenomena, but their molecular roles in asthma pathogenesis are unclear. It was found that among oxidatively modified DNA bases, 8-oxoguanine (8-oxoG) is one of the most abundant, and its levels in DNA and body fluids are considered a biomarker of ongoing asthmatic processes. Free 8-oxoG forms a complex with 8-oxoG DNA glycosylase-1 and activates RAS-family GTPases that induce gene expression to mobilize innate and adaptive immune systems, along with genes regulating airway hyperplasia, hyper-responsiveness, and lung remodeling in atopic and nonatopic asthma. Summary DNA's integrity must be maintained to prevent mutation, so its continuous repair and downstream signaling 'fuel' chronic inflammatory processes in asthma and form the basic mechanism whose elucidation will allow the development of new drug targets for the prevention/reversal of lung diseases.